The influence of whole-body cryotherapy or winter swimming on the lipid profile and selected adipokines - Bartłomiej Ptaszek; Szymon Podsiadło; Artur Wójcik; Olga Czerwińska-Ledwig; Aneta Teległów (BMC, 2023)
Abstract Purpose The aim of this study was to investigate the effect of a series of 20 whole-body cryotherapy (WBC) sessions and 20 winter swimming sessions on the lipid profile and selected adipokines. Materials/methods The experimental group consisted of 30 people who underwent a series of WBC treatments and 30 people who underwent a winter swimming. The control group consisted of 30 people - without intervention. Study 1: on the day of the commencement of whole-body cryotherapy / at the beginning of the winter swimming season; and Study 2: after a series of 20 cryotherapy sessions / at the end of the winter swimming season. The control group was also tested twice (4-week break). There were 20 WBC treatments − 5 times a week (4 weeks) and 20 cold water baths - once a week (20 weeks). Results A statistically significant increase in the concentration of adiponectin, resistin and leptin in women and resistin and leptin in men was observed after the winter swimming season. Differences were also found in the second study between the groups of women using WBC and the control group, as well as the groups of women swimming and the control group. In men, however, these differences were observed in WBC and the control group. The significance level of α = 0.05 was adopted in the analyzes. Conclusions The use of WBC may changes in the lipid profile and selected adipokines in men. Regular winter swimming may changes of selected adipokines in both women and men.